-2y-11=-6y+13

Simple and best practice solution for -2y-11=-6y+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2y-11=-6y+13 equation:


Simplifying
-2y + -11 = -6y + 13

Reorder the terms:
-11 + -2y = -6y + 13

Reorder the terms:
-11 + -2y = 13 + -6y

Solving
-11 + -2y = 13 + -6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6y' to each side of the equation.
-11 + -2y + 6y = 13 + -6y + 6y

Combine like terms: -2y + 6y = 4y
-11 + 4y = 13 + -6y + 6y

Combine like terms: -6y + 6y = 0
-11 + 4y = 13 + 0
-11 + 4y = 13

Add '11' to each side of the equation.
-11 + 11 + 4y = 13 + 11

Combine like terms: -11 + 11 = 0
0 + 4y = 13 + 11
4y = 13 + 11

Combine like terms: 13 + 11 = 24
4y = 24

Divide each side by '4'.
y = 6

Simplifying
y = 6

See similar equations:

| 12-2(a-1)=8+a | | 142-5x=4x+7 | | 11a-1=6a+9 | | (2x+1)(2x+1)-(2x-1)(2x-1)=(x+6)(x+6)-(x)(x) | | 2x^3+2x-12x=0 | | 8a+23=4a+51 | | x^3+13=0 | | 11a-2=4a-51 | | x=3-2+8 | | x^2-24x+128=0 | | 3-1+5= | | x-10-9=8 | | ln(1-3x)+3=9 | | 3G+5=11 | | ln(x+7)=4 | | 5f=25 | | x+2=100 | | 0.04x-0.20(50+x)=-0.04(50) | | 2n+3= | | (z^3)+13=0 | | z^3+13=0 | | 9-3y=0 | | 8x-36=6x-10 | | 3(7+2x)+2(1-x)=19 | | 4(3y-5)+(y+2)= | | x^4-5x^3-3x^2+45x-54=0 | | p-2+5p=2p-6 | | 4r+6= | | 3x-108=108-6x | | 1.5(2x+4*4)=56 | | 4x-2=3x+9x | | 3x*6=50 |

Equations solver categories